Rapid-Onset Obesity with Hypoventilation, Hypothalamic, Autonomic Dysregulation, and Neuroendocrine Tumors (ROHHADNET) Syndrome: A Systematic Review. (21st November 2018) - Lee, Jiwon M.; Shin, Jaewon; Kim, Sol; Gee, Heon Yung; Lee, Joon Suk; Cha, Do Hyeon; Rim, John Hoon; Park, Se-Jin; Kim, Ji Hong; Uçar, Ahmet; Kronbichler, Andreas; Lee, Keum Hwa; et al.
Abstract : Background and Aim . ROHHADNET (rapid-onset obesity with hypoventilation, hypothalamic, autonomic dysregulation, neuroendocrine tumor) syndrome is a rare disease with grave outcome. Although early recognition is essential, prompt diagnosis may be challenging due to its extreme rarity. This study aimed to systematically review its clinical manifestation and to identify genetic causes. Materials and Methods . We firstly conducted a systematic review on ROHHAD/NET. Electronic databases were searched using related terms. We secondly performed whole exome sequencing (WES) and examined copy number variation (CNV) in two patients to identify genetic causes. Results . In total, 46 eligible studies including 158 patients were included. There were 36 case reports available for individual patient data (IPD; 48 patients, 23 ROHHAD, and 25 ROHHADNET) and 10 case series available for aggregate patient data (APD; 110 patients, 71 ROHHAD, and 39 ROHHADNET). The median age at onset calculated from IPD was 4 years. Gender information was available in 100 patients (40 from IPD and 60 from APD) in which 65 females and 35 males were showing female preponderance. Earliest manifestation was rapid obesity, followed by hypothalamic symptoms. Most common types of neuroendocrine tumors were ganglioneuromas. Patients frequently had dysnatremia and hyperprolactinemia. Two patients were available for WES. Rare variants were identified in PIK3R3, SPTBN5, and PCF11 in one patient and SRMS, ZNF83, and KMT2B in another patient, respectively. However, there was no surviving variant shared by the two patients after filtering. Conclusions . This study systematically reviewed the phenotype of ROHHAD/NET aiming to help early recognition and reducing morbidity. The link of variants identified in the present WES requires further investigation.